Census estimates of algal and epiphytic carbonate production highlight tropical seagrass meadows as sediment production hotspots - Perry, Chris T. (2019)
Tropical shelf, platform and reef-lagoon systems are dominated by calcium carbonate (CaCO3) sediments. However, data on habitat-specific CaCO3 sediment production rates by different sediment producing taxa are sparse, limiting understanding of where and in what form CaCO3 sediment is produced, and how overall sediment budgets are influenced by habitat type and scale. Using novel census methodologies, based primarily on measures of plant biovolumes and carbonate content, we assessed habitat-scale production by two ubiquitous biogenic CaCO3 sediment producers, calcareous green algae and seagrass epiphytes, across southern Eleuthera Bank, Bahamas (area ∼140 km2). Data from species-specific plant disaggregation experiments and from X-ray diffraction (XRD) analysis of calcified plants also allowed us to resolve questions about the size fractions and mineralogies of the carbonates produced. Production rates varied significantly among habitats (range: 1.8–237.3 g CaCO3 m−2 yr−1), collectively totaling ∼0.98 M kg annually across the study area. Outputs comprise similar amounts of aragonite and high Mg-calcite, with ∼54% of the CaCO3 produced being contributed as mud-grade (<63 μm) sediment. Our analysis also reveals that habitat type and extent – especially of medium and high density seagrass beds - strongly influence the amounts and types of carbonate sediment generated. Dense seagrass beds were identified as the dominant per unit area production sites, contributing ∼17% of total CaCO3 despite covering only 0.5% of the study area. These findings have direct relevance for quantifying present-day sediment budgets and for predicting changes in sediment generation at the system scale in responses to modified habitat extent and productivity.